"We've Tamed the World by Framing It" : Islam, 'Justifiable Warfare,' and situational responses to the war on terror in selected post-9/11 novels, films and television - Sulter, Philip Eric John (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
This thesis explores geopolitically diverse fictional responses to 9/11 and the War on Terror. Drawing on Judith Butler's (2009) notion of the "frames of war," Jacques Derrida's (2005) conception of the 'friend'/'enemy' binary, and Mahmood Mamdani's (2004) critique of the 'good' Muslim, 'bad' Muslim dichotomy (delineated in 2001 by President George W. Bush) I examine how selected examples of contemporary literature, as well as a popular television series, depict the War on Terror; and analyse how these differently situated texts structure their respective depictions of Islam and Muslims. In the first chapter, I focus on how The Reluctant Fundamentalist (2007), a novel by the Pakistani author, Mohsin Hamid, problematises the 'good' Muslim, 'bad' Muslim binary, and argue that the protagonist's decision to leave the United States in the wake of 9/11 represents an important political comment on global perceptions of American foreign policy and the human cost of millennial capitalism. Chapter 2 is an investigation of two novels: The Silent Minaret (2005) and I See You (2014), by the South African writer, Ishtiyaq Shukri. By situating his characters in a variety of geopolitical spaces and temporal realities, Shukri encourages the reader to discard the structuring frames of nation, race, and religion, and links the vulnerability and violence implicit in the War on Terror to a longer history of conquest, colonialism, and apartheid. In the process, Shukri illustrates the importance of understanding repressive local contexts as interwoven with global and historical power dynamics. Chapter 3 is a study of the popular American television series, Homeland (2011"”), created by Alex Gansa and Howard Gordon, and focuses on the manner in which the Central Intelligence Agency's "Overseas Contingency Operations" are portrayed by the show. I argue that Homeland initially problematises the 'friend'/'enemy' binary, but subsequently collapses into a narrative in which these two polarities are construed by prevailing American attitudes towards Islam and the notion of the War on Terror as a necessity. This thesis concludes that texts that characterise the War on Terror as a global phenomenon, and situate it within a broad historical discourse, are able to subvert the singularity ascribed to the 9/11 attacks, as well as the epochal connotations of the 'post-9/11 ' literary genre. I argue that the novels I have chosen scrutinise the ways in which perceptions are framed by dominant forms of media, historiography, and political rhetoric, and not only offer unique insights on the repercussions of the global War on Terror but attempt to conceive of humanity in its totality, and therefore destabilise the ontological and reductive operation of the frame itself.
Keywords: Uncatalogued